Expression Scale Emotional Family: Validity and Reliability Study in Families with Patient Schizophrenia - Ardika, Noviana Ayu; Cahyati, Widya Hary (Universitas Negeri Semarang, 2025)
This study aims to determine the validity and reliability of the short version of the Level of Expressed Emotion (LEE) Scale in measuring family emotional expression toward individuals with schizophrenia. A quantitative approach with a descriptive correlational design was employed. A total of 18 respondents were purposively selected from families living with schizophrenia patients. The instrument consisted of two subscales: Critical Comments and Emotional Overinvolvement. Validity testing revealed that all items in both subscales had correlation coefficients greater than the critical value (r > 0.443) and were statistically significant at p < 0.05. Reliability testing yielded Cronbach's Alpha values of 0.934 for Critical Comments and 0.866 for Emotional Overinvolvement, indicating high internal consistency. Therefore, the short version of the LEE Scale is a valid and reliable tool to assess family emotional expression that may influence relapse in individuals with schizophrenia.